Ghosts of the African Diaspora Re-Visioning History, Memory, and Identity - Chassot, Joanne (Re-Mapping the Transnational: A Dartmouth Series in American Studies, 2018)
The first monograph to investigate the poetics and politics of haunting in African diaspora literature, Ghosts of the African Diaspora: Re-Visioning History, Memory, and Identity examines literary works by five contemporary writers-Fred D'Aguiar, Gloria Naylor, Paule Marshall, Michelle Cliff, and Toni Morrison. Joanne Chassot argues that reading these texts through the lens of the ghost does cultural, theoretical, and political work crucial to the writers' engagement with issues of identity, memory, and history. Drawing on memory and trauma studies, postcolonial studies, and queer theory, this truly interdisciplinary volume makes an important contribution to the fast-growing field of spectrality studies.